ENTRE O PÚBLICO E O PRIVADO: DISCURSOS SOBRE O PLANEJAMENTO FAMILIAR NO ESPAÇO URBANO - Vaz, Cleunice (2015)
The present work was developed according to the theorical and methodological contribution of the Analysis of the Speech pecheutiana and had by study object the family planning. Passed by speeches that come from several domains, speechly, we took the family as a political institution, that dwels the urban space and that is not exempt of the State regulations, that by the Wind Language, influences and determines the existential conditions of this secular institution. The corpus was compound by six materialities that made part from the Campaigns of Family Planning promoted by the Central Government and tutored by the Health Department, in the beginning of the XXI century, and produced the effect of the sense, sometimes of alert (need to planning how many and when to have children), sometimes of threat (calling the character-teenager, the health professionals and the couples, and more specifically, the character-female, about the losses from an undesired pregnancy). Burst into the selected materialities, the authoritarian speech, for the Government/Health Department delets his connection with the speaker (character/family), ordering very strongly what he should/should not do to plan the family and avert the pregnancy, besides the assistant speeches, that place the State in the position of the benefactor, who protects and provides to the character the rights and resources necessary to a good quality of life, and, therefore, knows what is/is not good to him. Then, there is a contradictory tension between democracy (respect to the character decision) and authoritarianism (the use of the imperative) in the analysed materialities. So we certified that the axle of the public (street) crosses the axle of the private (house), produceing the consensus, that support the public politics, in the contemporary societies called democratic and that, by means of the Wind Language, the State acts on the "masses", feigning the real, individualizing the character by means of the institutions and speeches. Saying in the other way, the family suffers the regulation and the interference of the State, that searches to control the urban space and submit itself to the practices demanded by the government, to the detriment of the wishes and particular interests and continue lacking good public services.